Restorative nodes of governance in the Anthropocene: Iran's Kashaf River. (15th August 2021) - Braithwaite, John; Hojabrosadati, Honeye; Forsyth, Miranda
Abstract: This article describes an environmental crisis in Iran that is actually a multidimensional crisis of law and policy. The article explores the restorative nodal governance response to such polycentric problems by weaving together five related ideas originating from criminologist and regulatory scholar Clifford Shearing: nodal governance; regulatory culture as a storybook (rather than a rulebook); justice as a better future; networked discovery of Awareness, Motivation, and Pathways for transformation; and a green ethic of care to guide transformation. We use an imaginary of a river to learn from a confluence of these ideas. They involve nodes of local governance organized by front‐line workers who restoried intertwined problems with an ethic of care. The challenge uncovered is that restorative microstrategies proved promising when steering powerless actors, but frayed when faced with factory owners. More aggressive strategies of nodal governance may bring forth more responsive escalation in order to confront privilege. Yet such strategies might be more creatively escalated as nodes of conversational regulation that reconfigure Shearing's five insights to transform landscapes of power. A coherence discovered inductively across these insights revolves around restorative nodal contestation of hegemony. Even lives as infused with domination as those found along the Kashaf River in Iran, where our case study is set, can be restored in counterhegemonic ways.